(untitled) (KASBIT Business Journal, 2017)
In the current era according to the floating industrial ratings the top most industry of Pakistan is the cement industry. This sector has been able to earn high returns over the investment which has created more interest to determine major factors which are needed to be focused on while evaluating the profitability of the cement companies. DuPont Model was one of the most significant equation presented in 70’s which stated that Returns on Assets (ROA) is to be considered for evaluating firm’s performance but later the researchers figured out that Return on Equity (ROE) is the major factor which should be considered for assessing profitability and growth of the company. The purpose of the study is to investigate the most influencing factors which affect the Returns on Equity (ROE) for the cement sector of Pakistan. Data from 2006 to 2015 is taken for the analysis from annual reports of 03 listed cement companies in Pakistan Stock Exchange. Regressions model with the Panel Least Squares method and Period random effects will be used for the measurement of the data. The results of this research will be beneficial for future researchers who aim to focus on investigating the determinants of the Return on Equity (ROE). The study will also describe the impact of various financial ratios on ROE which will also assist cement companies to work on their full potential and acquire large market share which will ultimately result in better profitability. The research is concluded with the recommendations and suggestions for the selected companies and this study provides tool for companies to identify the main factors of the return on equity.